9 – (–2) + (–5) =

14 + (–3) – (–8) =

–5 – (–8) + (–25) =

–3 + (–7) + (–19) =

23 + (–22) – (–25) =

17 + (–2) + (–5) =

–25 – (–6) + (–9) =

9 + (–2) + (–9) =

–23 – (–23) + (–15) =

–1 + 16 + (–8) =

9 – 23 + (–9) =

4 – (–18) – (–3) =

19 – 21 – (–5) =

7 + (–11) + (–6) =

16 – (–14) + (–8) =

–28 + (–11) – (–28) =

мирок3 мирок3    2   17.04.2020 16:41    0

Ответы
mobilion2016 mobilion2016  02.08.2020 09:52

Пошаговое объяснение:

9 – (–2) + (–5) = 6

14 + (–3) – (–8) =19

–5 – (–8) + (–25) = -22

–3 + (–7) + (–19) = -29

23 + (–22) – (–25) = 26

17 + (–2) + (–5) = 10

–25 – (–6) + (–9) = -28

9 + (–2) + (–9) = -2

–23 – (–23) + (–15) = -15

–1 + 16 + (–8) = 7

9 – 23 + (–9) = -23

4 – (–18) – (–3) = 25

19 – 21 – (–5) = 3

7 + (–11) + (–6) = -10

16 – (–14) + (–8) = 22

–28 + (–11) – (–28) = -11

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика